Histopathological Alterations in Ovarian and Uterine Treated with Extract and Fraction of Kebar Grass (Biophytum petersianum) - Nina Herlina; Mulyati Effendi; Wilda Nurhikmah; Yulianita Yulianita; Fitri Aninda (Universitas Pakuan, 2022)
Kebar grass (Biophytum petersianum) is being used traditionally by the people of West Papua to increase fertility. The effects of extracts and fractions of Kebar grass on the estrus cycle duration and estrus phase in rats were evaluated. The present work was designed to investigate the effects of administration of kebar grass extract and its fraction on the histopathological changes in the ovaries and uterine of rats. The female rats were treated with carboxy methyl cellulose sodium (CMC sodium) 1 % (group I), ethynile estradiol (group II), extract kebar grass (group III), n-hexane fraction (group IV), ethyl acetate fraction (group V), and water fraction (group VI) of kebar grass via gavage daily for 7 days. At days 7th and 14th, 3 rats in each group were euthanized. Uterine and ovarian collected and weighed. Hematoxylin-Eosin staining and the paraffin technique were used for histological preparation. Data were analyzed by One Way ANOVA followed by the Duncan test. The Kebar grass has an effect to increase ovarian and uterine weight, increasing most of the number of follicles especially primary follicle and uterine thickness. The treatment with ethyl acetate fraction of kebar grass (group V) constantly showed more effective results than the other kebar grass treatment.